Supraclavicular Vs Infraclavicular Approaches of Brachial Plexus Block Using Nerve Stimulator With 30ml Of 0.5% Levobupivacaine and 50µg Dexmedetomidine (Prospective Comparative Analytical Study) - Balwinder Kaur Rekhi; Parmod Kumar; Mandeep Kaur; Gurdeep Singh; Manjeet Singh (GMC Patiala Journal of Research and Medical Education, 2021)
Introduction : Regional Anaesthesia technique for pain relief with peripheral nerve block is devoid of side effects such as nausea, vomiting, polypharmacy, haemodynamic instability and voiding difficulty inherent to general anaesthesia and provide post-operative analgesia. Aims : To Compare the ease of technique and efficacy of block between supracvlavicular and infraclavicular approaches for brachial plexus block using nerve stimulator. Material And Methods : Sixty Patients of age group between 18 to 65 years with asa grade 1 and 2 undergoing upper limb surgeries were randomly allocated into two groups : group sc and group ic. each patient received 30ml of 0.5% levobupivacaine and 50µg of Dexmedetomidine. Parameter observed were-block performance time, onset of sensory and motor block, duration of block, duration of analgesia, complication ,quality of block and patient satisfaction. Results : The Results Shows the significant difference in mean time of onset of sensory block. the mean time of onset of sensory block in group ic was 13.17 min and 15.67 min in group sc(p value 0.035).4 patients in group sc had accidental vascular puncture and none in group ic with significant difference in p value i.e 0.038. time to perform block, time of onset of motor block, duration of analgesia and patient satisfaction were not significant in group sc and group ic. Conclusion : It was concluded that onset of sensory block in infraclavicular group was statistically significantly earlier with less incident of vascular puncture compared to supraclavicular group using nerve stimulator.